Comparative oncology: The paradigmatic example of canine and human mast cell neoplasms. (24th September 2018) - Willmann, Michael; Hadzijusufovic, Emir; Hermine, Olivier; Dacasto, Mauro; Marconato, Laura; Bauer, Karin; Peter, Barbara; Gamperl, Susanne; Eisenwort, Gregor; Jensen‐Jarolim, Erika; Müller, Mathias; Arock, Michel; et al.
Abstract : In humans, advanced mast cell (MC) neoplasms are rare malignancies with a poor prognosis. Only a few preclinical models are available, and current treatment options are limited. In dogs, MC neoplasms are the most frequent malignant skin tumours. Unlike low‐grade MC neoplasms, high‐grade MC disorders usually have a poor prognosis with short survival. In both species, neoplastic MCs display activating KIT mutations, which are considered to contribute to disease evolution. Therefore, tyrosine kinase inhibitors against KIT have been developed. Unfortunately, clinical responses are unpredictable and often transient, which remains a clinical challenge in both species. Therefore, current efforts focus on the development of new improved treatment strategies. The field of comparative oncology may assist in these efforts and accelerate human and canine research regarding diagnosis, prognostication, and novel therapies. In this article, we review the current status of comparative oncology approaches and perspectives in the field of MC neoplasms.